Home gardens: a source of health in the home (Research, Society and Development, 2021)
Home gardens are considered a source of health at home, as the cultivation and consumption of vegetables rich in nutrients and bioactive compounds help in the prevention and treatment of various diseases. The objective of this review is to highlight technical information about the types and classifications of existing gardens, characterizing each one of them and illustrating some aromatic vegetables and their demands to be cultivated in small areas. Articles, books, and other materials were used in the elaboration of the narrative review. Brazilian cuisine is very diverse, and has vegetables with different colors, nutrients and bioactive compounds important for body metabolism. Gardens are classified according to their type (production, educational and mixed); location (rural and urban); responsible (community and individual); type of management (conventional and organic); and layout (vertical and horizontal). The vegetable garden is an element that promotes healthy habits and lifestyle, both individual, family or collective, considered important in the prevention/treatment of chronic non-communicable diseases associated with poor diet. It is concluded that growing vegetables at home, in addition to bringing health benefits, can become a hobby and transform the home into a welcoming environment with greater contact with nature.